2018
DOI: 10.1111/dsji.12147
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Customer Experience Quality and its Significance in Retail Management: A Role Playing Game using Chinese Puzzle ‘Tangram’

Abstract: Services are intangible in nature. For a marketing educator, it is difficult to illustrate to students the means of creating favorable customer experiences through standard lectures or case studies in a services context, considering this intangibility property. This paper describes a simple role playing game that uses the Chinese puzzle 'Tangram' to help students comprehend how customer experiences are shaped within and beyond a service setting. In the game, the class gets divided into two groups, individual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Motivating students so that they can understand the importance of integrated-topic scenarios is another issue of concern (Chang et al , 2009). Therefore, the courses taught at educational institutions are changing their teaching patterns and utilize comprehensive learning solutions instead of focusing on subject knowledge only (Ten Eyck, 2011; Preziosi and Alexakis, 2011; Tran and Lewis, 2012; Westrup and Planander, 2013; Tabak and Lebron, 2017; Paul and Ponnam, 2018). For instance, in order to determine the quantities to produce, managers need to consider their decisions with regard to demand forecasting, allocation of resources and inventory policy as well as scheduling of manpower and machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Motivating students so that they can understand the importance of integrated-topic scenarios is another issue of concern (Chang et al , 2009). Therefore, the courses taught at educational institutions are changing their teaching patterns and utilize comprehensive learning solutions instead of focusing on subject knowledge only (Ten Eyck, 2011; Preziosi and Alexakis, 2011; Tran and Lewis, 2012; Westrup and Planander, 2013; Tabak and Lebron, 2017; Paul and Ponnam, 2018). For instance, in order to determine the quantities to produce, managers need to consider their decisions with regard to demand forecasting, allocation of resources and inventory policy as well as scheduling of manpower and machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Lemke et al [21] characterize experience quality as perceived perfection or superiority from the obtained experience. Similarly, Paul and Ponnam [22] found that consumer experience quality has a positive relationship with the value provided by individuals at a service or product purchasing point. Driver and Tocher [23] stated that recreational activity experiences include experience obtained by individuals from activities, entertainment, individual feedback and selection of activities they are interested in with freewill.…”
Section: Experience Qualitymentioning
confidence: 92%
“…The approach is thought to resonate with millennial students (Poole et al, 2014) and, more recently, has been shown to increase student engagement (e.g., Dias, 2017). It has been used to teach concepts in data systems (Yang & Guo, 2020), learning curves (Robbins, 2019), entrepreneurship (Isabelle, 2020), transportation (Rossetti, 2018), customer experience quality (Paul & Ponnam, 2018), and externalities (Giraud-Carrier & Schmidt, 2015), among others. What are game elements?…”
Section: Game Elements In Pblmentioning
confidence: 99%